Costs to provide a tobacco cessation intervention with parents of pediatric emergency department patients - Akers, Laura (Tob Prev Cessat, 2020)
INTRODUCTION: Pediatric emergency department (PED) visits are opportune times in which to provide smoking cessation interventions for parents who smoke. This study reports on the costs of providing parental smokers who bring their children to the emergency setting, with a screening, brief intervention, and assisted referral to treatment (SBIRT) intervention, which includes counseling about tobacco cessation and nicotine replacement therapy. METHODS: Cost data were collected during a randomized controlled trial with 750 parental smokers whose child was presented to a PED or pediatric Urgent Care unit with a potential tobacco smoke exposure-related illness. Interventionist training, screening, and SBIRT costs are reported from the organizational perspective (i.e. that of the providing hospital). A spreadsheet tool was created to allow for organizations to estimate their own costs based on their settings, for each aspect of the intervention. RESULTS: The mean costs per parent included interventionist training, screening and enrollment, SBIRT delivery, distribution of take-home materials and nicotine replacement therapy, booster text messages, and follow-up phone contact. The total cost per parent was approximately $97. Varying the underlying cost assumptions led to total costs ranging from $85 to $124 per treated parent. CONCLUSIONS: The emergency setting is an important locus of tobacco control that could have a large public health benefit to parents and children. The costs reported in this report and the accompanying spreadsheet tool will permit emergency settings to estimate the costs and assist with planning, staffing and resource allocation necessary to implement an SBIRT smoking cessation intervention in research-based and clinically-based cessation interventions into adult or pediatric emergency visits.